Child psychopathic traits moderate relationships between parental affect and child aggression - Yeh, Michelle T. (2011)
OBJECTIVE: Previous studies show that children with psychopathic traits may be less responsive to parenting. While harsh/inconsistent parenting is associated with increased problem behaviors in children low on psychopathic traits, children high on psychopathic traits show consistently high levels of problem behavior regardless of negative parenting. Moderating effects of child psychopathy on positive dimensions of parenting have not been explored. METHOD: We applied multi-level regression models to test for interactions between child psychopathic traits and both positive and negative parental affect on individual differences in both reactive and proactive aggression in a community-based sample of 1,158 children aged 9–10. RESULTS: There were significant associations between psychopathy, and positive and negative parental affect with both forms of aggression. Child psychopathic traits also moderated effects of positive and negative parental affect. Children low on psychopathic traits showed decreasing reactive aggression as positive parental affect increased, and increasing levels of reactive aggression as negative parental affect increased, but children high on psychopathic traits showed more stable levels of reactive aggression regardless of levels of parental affect. Proactive aggression was more strongly associated with negative parental affect among children with higher levels of psychopathic traits. CONCLUSIONS: In a community sample of pre-adolescent children, child psychopathic traits were shown to moderate the effects of parental affect on aggression. Reactive aggression in children high on psychopathic traits appears less responsive to variations in either positive or negative parenting. In contrast, child psychopathic traits may exacerbate the effects of high levels of negative parental effect on proactive aggression.